Effect of hydrogen addition on performance and emission characteristics of a common-rail CI engine fueled with diesel/waste cooking oil biodiesel blends - FEYZİOĞLU, AHMET; YILMAZ, İLKER TURGUT (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, the effect of hydrogen addition to a compression ignition (CI) engine fueled with the diesel fuel-waste cooking oil biodiesel (WCOB) blend (B25) on the engine performance, and exhaust emissions was examined experimentally. In the tests, a four-cylinder, four-stroke, water-cooled, 1.461-L, turbocharged CI engine was used. The engine tests were performed at the fixed engine speed of 1750 rpm and at the diverse engine loads of 40, 60 and 80 Nm. The hydrogen was added to the intake air at the flow rates of 10, 20, 30 and 40 lpm. According to the results obtained, hydrogen had a positive effect on break specific fuel consumption (BSFC) for all test conditions. The increase occurred at the exhaust gas temperatures (EGTs) and cylinder pressures (CPs) with hydrogen addition. The NOx and total hydrocarbon (THC) emissions decreased with the hydrogen addition until 30 lpm at 40 and 60 Nm engine loads. On the other hand, they increased at 80 Nm engine load for all hydrogen additions. While CO2 and O-2 emissions decreased with the hydrogen addition, the smoke emissions increased. It was found that the value of 30 lpm was the optimum condition of the hydrogen addition rates. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: CI engine; Waste cooking oil biodiesel; Hydrogen enrichment; Engine performance; Cylinder pressure; Exhaust emissions